2006
DOI: 10.1088/0957-4484/18/1/015702
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Ag nanoparticles in SiO2at ambient conditions

Abstract: Abstract. The room temperature stability of nanometer-sized silver clusters in silica matrices has been investigated by following the temporal evolution of their surface plasmon absorption. Ag clusters in SiO 2 were prepared by either annealing silica samples doped with atomic silver or by co-deposition of pre-formed clusters of defined size. Clusters were found to be unstable at ambient conditions on a time scale of days to weeks, independent of preparation conditions. The disappearance of the plasmonic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 27 publications
1
35
1
1
Order By: Relevance
“…This implies a greater quantity of NPs with larger sizes and thus stability which would in turn oppose dissolution during ripening and as a consequence, E R,N > E D,N is possible. On the contrary, the air atmosphere promotes the occurrence of rather unstable particles owing to O 2 diffusion within the silica matrix [23]. Accordingly, during HT in the presence of O 2 , a greater quantity of NPs with smaller sizes and thus instability [22,23] would be attained which in turn would favor thermodynamically the particle dissolution during ripening, and as a consequence, E R,A < E D,A may result.…”
Section: Resultsmentioning
confidence: 99%
“…This implies a greater quantity of NPs with larger sizes and thus stability which would in turn oppose dissolution during ripening and as a consequence, E R,N > E D,N is possible. On the contrary, the air atmosphere promotes the occurrence of rather unstable particles owing to O 2 diffusion within the silica matrix [23]. Accordingly, during HT in the presence of O 2 , a greater quantity of NPs with smaller sizes and thus instability [22,23] would be attained which in turn would favor thermodynamically the particle dissolution during ripening, and as a consequence, E R,A < E D,A may result.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the Ag nanostructures are unstable and easily get oxidized. [39][40][41] Therefore, the as-deposited samples were kept in the vacuum condition. However, a strong increase in the oxidation resistance was observed with the increase of Au atomic fraction inside the nanostructures, 41 and it is reported that most of the Au-Ag nanostructures was not oxidized at gold fractions above 0.4 in solution.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a layer of oxide Ag (usually Ag 2 O) was formed on the nanospheroids surface, and the Ag-core Ag-oxide shell structure will induce a red shift of the characteristic surface plasmon resonance response for pure Ag, which located at around 400 nm. 39,40 However, this plasmon absorption peak was rather stable over time: after 8 months in a low vacuum condition, the plasmon absorption intensity has decreased a little (see S1 in the supplementary information 47 ).…”
Section: à2mentioning
confidence: 99%
“…These films were bright colored, transparent, stable and had characteristic SPR bands belonging to Ag or Au NPs. However, Ag clusters formed on disperse silica surface were found to be stable only for a few days [3]. The self-agglomeration and oxidation of Ag NPs were detected also within the porous silica films [12].…”
Section: Introductionmentioning
confidence: 97%
“…That is why developed silica surface covered with OH groups offers unique environment for the fixation and stabilization of nanosized silver and gold particles (Ag and Au NPs) for applications in optics, sensing, catalysis and as bactericides. However, Ag NPs are unstable on silica surface under ambient conditions due to fast oxidation [3]. It is important to prevent or inhibit the aggregation of NPs and oxidation process at the nanocluster formation stage, especially in case of silver.…”
Section: Introductionmentioning
confidence: 99%